Fit to context matters - Selecting and using information systems development methods to develop business in digitalization contexts - Dahlberg Tomi; Lagstedt Altti (United States, 2022)
We ponder the relations of software, information systems (IS) and business development methods in the development of digital businesses and in the digitalization of extant businesses. We present our published IS development method (ISDM) framework and its development. The framework is used as the background to reason the relations between the three development layers of digitalization: software, IS and business. We then propose six highly potential areas of future research. In addition, we answer to two research questions also paving the way to future research: is the matching of IS and business development context a reasonable proposition, and is the finding of extant literature true, according to which ISDMs are used limitedly in IS development work. We organized two workshops with 21 (14+7) participants to answer these questions. We detected yes and mixed answers. We contribute to research with the empirical findings and the proposed research areas.
Proceedings of the 54th Hawaii International Conference on System Sciences 2021